Using Evidence in L2 Argumentative Writing: A Longitudinal Case Study Across High School and University. Issue 1 (4th September 2016) - Kibler, Amanda K.; Hardigree, Christine
Abstract : This 8‐year longitudinal case study of Fabiola, a Spanish‐English bilingual, investigated her argumentative writing development, focusing on her use of evidence to support and develop arguments over time from high school through university. Data sources included 36 writing samples. Texts across grade levels and course types were analyzed to determine changes in evidential types (quotations and paraphrases), evidential functions, and reporting verbs used to introduce evidence. Interview transcripts were analyzed to identify Fabiola's changing perspectives on use of evidence in argumentative writing. Evidentials were found to vary according to course type, but more dramatic changes (in type, function, and range of reporting verbs used) were found over time as language proficiency and writing expertise developed, providing longitudinal support for other studies that have examined writers at only one point in time.